Effectiveness of E-Learning in the Field of Biochemistry - Ranjit Ambad; Archana Dhok; Roshan K. Jha (Journal of Pharmacy and Bioallied Sciences)
E-learning has gradually become tolerated in the teaching and learning process in higher learning institutions as one of the main learning aids, which enable learners get access to so many resources with so much ease. As in the field of biochemistry, in which concepts are complex and procedures are integral to the information, e-learning has its advantages and drawbacks. This study was designed with the intention to examine the suitability of e-learning model in the context of biochemistry course, more specifically, it was to identify the extent to which digital learning environment supports students’ understanding and real-life use of biochemical knowledge. Quantitative research comprises of the use of Survivors to obtain numerical data concerning the success of e-learning platforms concerning biochemistry. A survey is designed to have closed questions (such as the Likert scale) as well as demographic questions to capture. Closed questions measure participants’ views on e-learning tools, its utility and instructional usefulness as well as the demographic questions, which give a précis of participant profile and their past experiences in e-learning. The learning objectives laid down for the course were specific, measurable, and generic and included topics, such as enzyme kinetics, metabolic pathways, and protein structures. These were grouped into topic-based weekly work schedule. These sessions revealed that students who were attending the biochemistry courses are different, in that 71% of them agreed that the learning objectives for each of the modules, which were at the start of the course, served as a useful guide for understanding biochemistry as the learning objectives were well outlined at the start of the course. In about and through all of these recommendations, educational institutions will be able to design a more responsive and fair-blended e-learning environment that fosters success among learners and advanced understanding of biochemistry.